Separation of Hafnium From Zirconium by Anion Exchange - Hague, John L. (J Res Natl Bur Stand A Phys Chem, 1961)
The results of a systematic survey of the elution of hafnium and zirconium in diluted sulfuric acid, and in solutions of hydrochloric and sulfuric acids in water, are presented. The data characterize the behavior of the sulfate anion complexes of these elements on a strong quaternary-amine anion-exchange resin column. The possibility of separating these elements is demonstrated.